(untitled) (Revista Psicología y Sociedad, 2025)
The armed conflict in Cauca has had a devastating impact on Indigenous, Afro-descendant, and peasant women, who have faced multiple forms of violence and exclusion. Among the main aggressions are forced displacement, sexual violence, and the loss of their means of livelihood. These forms of violence not only physically affect women but also create profound psychological and cultural scars that are transmitted intergenerationally, perpetuating trauma within communities. The concept of cultural trauma is essential to analyzing these experiences, as it describes how catastrophic events transform the collective identity of a community. Women in Cauca have endured trauma that combines the impact of the armed conflict with historical structures of oppression, such as patriarchy, racism, and territorial dispossession. For Afro-descendant communities, these experiences are marked by a legacy of slavery and exploitation, while for Indigenous communities, they represent an extension of colonial processes.